Tracking structural transitions of bovine serum albumin in surfactant solutions by fluorescence correlation spectroscopy and fluorescence lifetime analysis. Issue 12 (28th March 2015) - Zhang, Xuzhu; Poniewierski, Andrzej; Hou, Sen; Sozański, Krzysztof; Wisniewska, Agnieszka; Wieczorek, Stefan A.; Kalwarczyk, Tomasz; Sun, Lili; Hołyst, Robert
<x xml:space="preserve">Abstract</x> Sudden structural changes of BSA in surfactant solutions are observed from FCS curves.